Modelling casino hospitality business cycles - Sheng, Li; Yin, Yechang; Zhang, Anning; Wu, Jiwei; Yang, Ziqing (Publishing House of Wroclaw University of Economics and Business, 2023)
This study decomposes the casino hospitality business cycles of Las Vegas and Macao into highgrowth states (HGS) and low-growth states (LGS) using a Markov switching model. The casino gaming sector in Macao experiences greater fluctuations than the sector in Las Vegas due to more volatility in tourism flows; that is, Macao has a slightly higher HGS and a considerably lower LGS than Las Vegas. Las Vegas’s hospitality cycle appears to be more robust than Macao’s, although both hospitality cycles are desirably asymmetric. Various factors, including external business cycles and supply-side factors, affect local hospitality cycles. In terms of policy suggestions, the study’s results suggest that promotional marketing must be strengthened in Las Vegas, and Macao must diversify its industrial base.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 33-41
Keywords: business cycle; hospitality cycle; casino gaming